(untitled) (Research, Society and Development, 2021)
Evidence of the use of medicinal plants comes since the beginning of humanity, as they used these plants to cure or treat people in their communities. Medicinal plants are defined as plants that have, in one or more organs, chemical constituents that can be used as therapeutic agents, as well as materials for the synthesis of drugs. This research aimed to investigate the popular knowledge on medicinal plants used to health promotion and cure illnesses in the community of Estreito, which is located eighteen kilometers from the city of Redenção do Gurguéia. A characterization study of the study area was carried out, seeking recognition of the area and an approximation with the resident population. Then, there were interviews with subjective questions and, finally, the third stage involved the photographic record of the botanical material using the free trail method. In this study a substantial number of species used for medicinal purposes was verified. Knowledge of ancestors is something that highlights the beneficial healing possible effects of medicinal plants in the Estreito community.